Pelatihan Analytical Hierarchy Process (AHP) Dengan Menggunakan Aplikasi Expert Choice V.11 - Siti Rofingatun; Rudiawie Larasati (The Community Engagement Journal, 2020)
Decision-making is already a part of life, sometimes we are confronted on two or more options, or easy choices to the hardest. At decision making involving a system (simple or complex), it is possible that decision making is done after a certain process. One of the decision-making tools that can be used is the Analytical Hierarchy Process (AHP) using the Expert Choice V. 11 application to solve complex problems by targeting a hierarchy of criteria, assessed subjectively by interested parties and then attracting various considerations to develop weights or priorities (conclusions). Therefore, there needs to be training for students of the accounting department of FEB-Uncen who are on the level of drafting their research plan to understand one of the analysis tools that will be expected to be applied by the students in his research.